Phase I Study of Afatinib and Selumetinib in Patients with KRAS‐Mutated Colorectal, Non‐Small Cell Lung, and Pancreatic Cancer. (29th December 2020) - Brummelen, Emilie M.J.; Huijberts, Sanne; Herpen, Carla; Desar, Ingrid; Opdam, Frans; Geel, Robin; Marchetti, Serena; Steeghs, Neeltje; Monkhorst, Kim; Thijssen, Bas; Rosing, Hilde; Huitema, Alwin; et al.
Abstract: Lessons Learned: Afatinib and selumetinib can be combined in continuous and intermittent dosing schedules, albeit at lower doses than approved for monotherapy. Maximum tolerated dose for continuous and intermittent schedules is afatinib 20 mg once daily and selumetinib 25 mg b.i.d. Because the anticancer activity was limited, further development of this combination is not recommended until better biomarkers for response and resistance are defined. Background: Antitumor effects of MEK inhibitors are limited in KRAS ‐mutated tumors because of feedback activation of upstream epidermal growth factor receptors, which reactivates the MAPK and the phosphoinositide 3‐kinase–AKT pathway. Therefore, this phase I trial was initiated with the pan‐HER inhibitor afatinib plus the MEK inhibitor selumetinib in patients with KRAS mutant, PIK3CA wild‐type tumors. Methods: Afatinib and selumetinib were administered according to a 3+3 design in continuous and intermittent schedules. The primary objective was safety, and the secondary objective was clinical efficacy. Results: Twenty‐six patients were enrolled with colorectal cancer ( n = 19), non‐small cell lung cancer (NSCLC) ( n = 6), and pancreatic cancer ( n = 1). Dose‐limiting toxicities occurred in six patients, including grade 3 diarrhea, dehydration, decreased appetite, nausea, vomiting, and mucositis. The recommended phase II dose (RP2D) was 20 mg afatinib once daily (QD) and 25 mg selumetinib b.i.d. (21 days on/7 days off) for continuous afatinib dosing and for intermittent dosing with both drugs 5 days on/2 days off. Efficacy was limited with disease stabilization for 221 days in a patient with NSCLC as best response. Conclusion: Afatinib and selumetinib can be combined in continuous and intermittent schedules in patients with KRAS mutant tumors. Although target engagement was observed, the clinical efficacy was limited.